Synthesis and characterization of catalytically active thiazolium gold(i)-carbenes. Issue 54 (22nd June 2017) - Dince, Clément C.; Meoded, Roy A.; Hilvert, Donald
Abstract : Thiazolium gold(i )-carbenes have been found to catalyze 5- endo -dig carbocyclization of an acetylenic dicarbonyl compound in organic solvents and hydroalkoxylation of an allene in aqueous buffer. Abstract : Thiamin analogs were used to synthesize mono gold(i )-carbene derivatives in a single step under aqueous conditions. The resulting thiazolium gold(i )-carbenes catalyze 5- endo -dig carbocyclization of an acetylenic dicarbonyl compound in organic solvents and hydroalkoxylation of an allene in aqueous buffer.